Dai radiofari ad EGNOS - Bernardini, Fabrizio (GEOmedia, 2010)
From radio beacons to EGNOS This article describes with images more than half a century of radio aids to air navigation. All the images, taken in the same location within Catania Fontanarossa airport, provides an historical perspective to the article about EGNOS and Civil Aviation published in the previous issue of GEOmedia.